eHealth platforms for promoting active living: a scoping review protocol (Research, Society and Development, 2022)
Introduction: In increasingly aging societies, the life course towards aging should be a positive experience supported by interventions for promoting healthy lifestyles, namely through social interaction. Technological advancements, such as eHealth platforms, are becoming increasingly available and may facilitate a more autonomous life and promote active and healthy living. Objectives: To map eHealth platforms designed and used to promote autonomous life and active aging. Methods: This scoping review will follow the JBI methodology for scoping reviews. Two independent reviewers will appraise the articles and extract and synthesize data. This review will include studies published in Spanish, English, and Portuguese, without any time restrictions. The following databases will be searched: MEDLINE (via PubMed), CINAHL Complete (via EBSCOhost), Scopus, Cochrane Database of Systematic Reviews (via EBSCOhost), SciELO, DART-Europe, CAPES, and MedNar.  Results: This scoping review is expected to include studies addressing eHealth platforms that promote autonomous life and active aging. Conclusion: This scoping review will analyze and synthesize the available scientific evidence on using eHealth platforms to promote autonomous life and active aging. It may also be the basis for a systematic review and/or help identify gaps where it may be important to invest in the future.